The Role of Oxidative Stress and Mutations of Mitochondrial DNA at Aging, Age Pathology, and Apoptosis - Pharmacorrection by Mitochondria-targeted Antioxidant SkQ1 - Tkachova, Oksana V (Asian Journal of Pharmaceutics (AJP), 2019)
There is presented the outcome analysis of numerous studies on the mechanisms of oxidative stress (OS) associated with increasing of the generation of reactive oxygen intermediate (ROI) in the electronic transport circuit of mitochondria, as well as the effect of ROI on the level of mutations in mitochondrial DNA (mtDNA). It is shown a fine sensibility of mtDNA to oxidative affections and mutations. The relation of age accumulation of mtDNA mutations with aging and life expectancy has been noted. It is also shown the relationship of OS with mtDNA mutations, apoptosis, diseases, and aging. It is considered a pharmacological way for the protection of ROI, aging, diseases, and prolonging life with the help of the antioxidant SkQ1, addressed directly to the mitochondria.